2011
DOI: 10.1136/jmedgenet-2011-100018
|View full text |Cite
|
Sign up to set email alerts
|

A role for XRCC2 gene polymorphisms in breast cancer risk and survival

Abstract: Background The XRCC2 gene is a key mediator in the homologous recombination repair of DNA double strand breaks. We hypothesised that inherited variants in the XRCC2 gene might also affect susceptibility to, and survival from, breast cancer. Methods We genotyped 12 XRCC2 tagging SNPs in 1,131 breast cancer cases and 1,148 controls from the Sheffield Breast Cancer Study (SBCS), and examined their associations with breast cancer risk and survival by estimating odds ratios (ORs) and hazard ratios (HRs), and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 50 publications
2
35
2
Order By: Relevance
“…There was no significant difference in the mean age at diagnosis between non-carriers and the carriers of the p.N457K haplotype (57.0 versus 56.7 years, respectively). Because some SNPs in double-strand break repair genes may impinge on prognosis rather than risk [25,26], we also assessed whether the rs74319927 haplotype could affect survival from breast cancer. In the 829 patients for whom follow-up data 21 22 22 22 22 22 22 22 22 22 22 22 22 22 21 22 21 22 (0.10) During the resequencing study, a total of four new missense substitutions were identified in the coding region, each of them in a single case (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference in the mean age at diagnosis between non-carriers and the carriers of the p.N457K haplotype (57.0 versus 56.7 years, respectively). Because some SNPs in double-strand break repair genes may impinge on prognosis rather than risk [25,26], we also assessed whether the rs74319927 haplotype could affect survival from breast cancer. In the 829 patients for whom follow-up data 21 22 22 22 22 22 22 22 22 22 22 22 22 22 21 22 21 22 (0.10) During the resequencing study, a total of four new missense substitutions were identified in the coding region, each of them in a single case (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The HaBCS includes a hospital-based series of 1012 unselected German breast cancer patients who were treated at the Department of Radiation Oncology at Hannover Medical School from 1996 to 2001. This patient series had been used previously to determine the frequency [17][18][19][20], to study some more common polymorphisms in candidate genes by the Breast Cancer Association Consortium [21][22][23][24] or for collaborative survival analyses [25,26]. Genomic DNA was available for 965 patients, and follow-up data were available for 829 patients, with a median follow-up time of 7.6 years.…”
Section: Patientsmentioning
confidence: 99%
“…Moreover, it has been proven that polymorphisms in XRCC2 may modify individual susceptibility to various types of cancer [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In candidate gene association studies, SNPs in or close to candidate genes are examined for their roles in breast cancer predisposition, governed by a hypothesisdriven approach. Several candidate gene association studies for breast cancer have been conducted during the last 10 years [Allen-Brady et al, 2006;Bewick et al, 2006;Haiman et al, 2008;Pooley et al, 2008;Sehl et al, 2009;Lin et al, 2011;Mangoni et al, 2011]; however, many of these studies were underpowered due to small sample size, resulting in inconsistent and irreproducible findings [Dunning et al, 1999;Pharoah et al, 2002]. To date, only 1 SNP (rs1045485) located in the coding region of CASP8 identified by a candidate gene association study has shown promise as a breast cancer predisposition risk factor .…”
Section: Candidate Gene Association Studiesmentioning
confidence: 99%
“…Initial genetic association studies for breast cancer were focused on interrogating a handful of SNPs in candidate genes or pathways such as DNA repair, apoptosis and cell-cycle checkpoints [Allen-Brady et al, 2006;Bewick et al, 2006;Mitra et al, 2008;Sehl et al, 2009;Economopoulos and Sergentanis, 2010;Lin et al, 2011;Mangoni et al, 2011]. Earlier this decade, completion of the Human Genome Project and the International HapMap Project, coupled with advances in genotyping technologies, made it possible to analyze the whole genome for SNPs associated with complex traits.…”
mentioning
confidence: 99%